1987
DOI: 10.1002/ajmg.1320270110
|View full text |Cite
|
Sign up to set email alerts
|

Proteus syndrome in Southern Africa: Natural history and clinical manifestations on six individuals

Abstract: Six individuals with Proteus syndrome have been investigated; 2 were adults and the others ranged in age from 2 to 11 years. They had a wide spectrum of manifestations and severity together with the hitherto unreported anomalies of penile hypertrophy, macro-orchidism, goiter, and failure of breast development. These findings were associated with normal endocrine function. Bizarre digital overgrowth, hemihypertrophy, thickened palms and soles, exostoses of the skull, and multiple hamartomata were common anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 7 publications
1
28
0
1
Order By: Relevance
“…Our patient had manifestations of the Proteus syndrome [Fay and Schow, 1968;Horton, 1971;Kontras, 1974;Cohen and Hayden, 1979;Temtamy and Rogers, 1976;Pawlaczyk and Sioda, 1976;Wiedemann et al, 1983;Lezama and Buyse, 1984;Gorlin, 1984;Burgio and Wiedemann, 1984;Costa et al, 1985;Muecke et al, 1985;Clark et al, 1987;Viljoen et al, 1987;Malamitsi-Puchner et al, 19871.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our patient had manifestations of the Proteus syndrome [Fay and Schow, 1968;Horton, 1971;Kontras, 1974;Cohen and Hayden, 1979;Temtamy and Rogers, 1976;Pawlaczyk and Sioda, 1976;Wiedemann et al, 1983;Lezama and Buyse, 1984;Gorlin, 1984;Burgio and Wiedemann, 1984;Costa et al, 1985;Muecke et al, 1985;Clark et al, 1987;Viljoen et al, 1987;Malamitsi-Puchner et al, 19871.…”
Section: Discussionmentioning
confidence: 92%
“…Recent reports review additional patients and manifestations of the Proteus phenotypes [Viljoen et al, 1987;Clark et al, 1987;Malamitsi-Puchner et al, 19871. As its name implies, this syndrome is quite variable but has its combination of distinctive anomalies.…”
Section: Wiedemann Et Almentioning
confidence: 97%
“…To the best of our knowledge, female pseudohermaphroditism has not been previously reported in the Proteus syndrome; however, Viljoen et al [1987] reported on a 2-year-old boy with the Proteus syndrome who had macro-orchidism and penile hypertrophy, without any other signs of virilization. Endocrine status was normal.…”
Section: Discussionmentioning
confidence: 70%
“…Riley-Smith syndrome, neurofibroma tosis, Wiedemann-Beckwith syndrome. Klippel-Trenaunay-Weber syndrome, cutis marmorata telangiectatica congenita, Cowden's disease, and nevus sebaceous of Jad assohn [17][18][19][20][21][22][23][24], In addition to their association with the aforementioned neurological syndromes, solitary scalp hamartomas may be confused with other scalp masses including communicating encephaloceles, meningoceles, cutaneous meningiomas, tumors of iatrogenic origin, scalp epidermoid tumors, fibroepithelioma of Pinkus, epithelioma of Malherbe, and more ominously, premalignant sebaceous nevi. angiosarcomas, and epithelioid sar coma [9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%